Utilización de microorganismos eficaces de origen natural, en el rendimiento, del cultivo de nabo (Brassica napus L.) en el Cantón Mocache. - Vargas Reyes, Liz Gabriela (2017)
The present work was carried out in the Experimental Farm "La María". The general objective of the present study was: to evaluate the effect of effective microorganisms in the soil and in the development of the turnip culture, in the Mocache canton. The doses used in this investigation were: 1) Without M.E .; 2) M.E. 0.40 Lha-1; 3) M.E. 0.60 Lha-1; 4) M.E. 0.80 Lha-1, which corresponded to the treatments under study in the Mocache area. The design Random Complete Blocks (BCA) with factorial arrangement of 2x4 + 1 in 3 repetitions was used. The Duncan test was applied at 95% probability to establish the statistical differences between the means of the doses for the area. The variables to be evaluated were: plant height, number of leaves, diameter, weight per plant, leaf area, yield and the economic analysis was carried out. Based on the research carried out and the analysis of the results, it was concluded that with the help of this research work, the positive effect of ME could be confirmed, directly favoring plant growth as observed in the variable height of silver with the different treatments. The organic fertilizer Agropesa + dose of M.E. 0.80 Lha-1 showed a higher data than the other treatments. When using earthworm humus the economic investment will be greater than using Agropesa and Jacinto de agua. Key words: Effective microorganisms (M.E), Performance.